Effect of magnetic field on dislocation morphology and precipitation behaviour in ultrafine-grained 7075 aluminium alloy. (10th December 2021) - Luo, Jun; Luo, Hongyun; Zhao, Tianshu; Wang, Runze
Highlights: The precipitation kinetics of alloy Ⅱ (thickness direction) is enhanced compared to that of alloy I (rolling direction). The magnetic field plays a positive effect on precipitation kinetics in alloy I because of retarding dislocation annihilation. The precipitation kinetics of alloy Ⅱ is suppressed by magnetic field attribute to the decline of dislocation density. The nucleation of η′ phase is promoted at the critical temperature (140 °C) due to the increase of activation energy. A highly efficient approach to investigate the precipitation kinetics of UFG Al alloys has been put forward. Abstract: The influence of magnetic field (1 T) on dislocation morphology and precipitation behaviour of ultrafine-grained (UFG) Al 7075 alloy was investigated after ageing from 90 to 200 °C via wide angle X-ray scattering (WAXS), small angle X-ray scattering (SAXS), and transmission electron microscopy (TEM). Experimental results reveal that the improved precipitation kinetics of alloys in the thickness plane (denoted as sample II) as compared to those in the rolling plane (denoted as sample I), which arises due to a higher dislocation density (morphology of dislocation cells) of the thickness plane than that of the rolling plane (morphology of dislocations and dislocation tangles). Specifically, because of different dislocation morphologies, the magnetic field positively and negatively affects the dislocation activity in samples I and II, leading to enhanced and suppressed precipitation behaviors, respectively. Interestingly, nucleation of the η′ phase is facilitated in the UFG alloy at the critical temperature (140 °C) because it affords a faster rate of atom diffusion and a higher dislocation density as compared to those exhibited by its coarse-grained alloy. This systematic and comprehensive study provides new insights into dislocation morphology and precipitation behaviour of the UFG 7075 Al alloy, while enabling the optimization of precipitation kinetics. Graphical abstract: Image, graphical abstract